Penggunaan Model Pembelajaran Problem Based Learning Dalam Meningkatkan Minat Belajar Siswa - Nadya Refita Sandi; Sahrun Nisa; Ari Suriani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
“Interest in learning is an important factor that influences the success of the learning process. One learning model that can be used to increase students' interest in learning is Problem Based Learning (PBL). This research aims to examine and analyze the effectiveness of implementing the PBL model in increasing students' interest in learning based on the results of literature studies. The method used is literature study, by collecting and analyzing relevant scientific articles, both published in national and international journals”. The articles studied are related to the application of the PBL model and its impact on students' interest in learning at various levels of education and subjects.The results of the analysis show that the PBL learning model has consistently proven to be effective in increasing students' interest in learning. Through a real problem-based learning process, students become more enthusiastic, motivated and actively involved in learning activities. Students also show higher curiosity and persistence in participating in learning. These findings indicate that the application of the PBL model can be an effective alternative for increasing students' interest in learning.